Factors influencing the preparedness of large unlisted companies to implement adapted international financial reporting standards in Portugal - Guerreiro, Marta Alexandra Silva (2012)
The Sistema de Normalização Contabilística [SNC] is the Portuguese title for the corpus of International Financial Reporting Standards [IFRS] that have been adapted for use in Portugal by unlistedcompanies. Based on an analytical framework that draws on aspects of new institutional theory, we surveyed 116 largeunlisted Portuguese companies in September 2009 to identify factors associated with their preparedness to implement the SNC. Generally, their degree of preparedness was low. Institutional factors that influenced the degree of preparedness positively included the participation of a parent company in conversion procedure decisions, the presence of exclusively Portuguese shareholders, the conduct of export activities, and mimetic behaviors. The results reveal that important insights can be obtained from complementing a study of isomorphic influences with the concepts of resistance and institutional logic. Though coercive and mimetic institutional factors influenced levels of preparedness positively, the preparedness process was undermined by resistance within the Portuguese accounting profession and by the embeddedness of code-law practices in the prevailing logic.